In situ U-Pb Isotope Dating Techniques for Sandstone-type Uranium Deposits - XIAO Zhi-bin; GENG Jian-zhen; TU Jia-run; ZHANG Ran; YE Li-juan; BI Jun-hui; ZHOU Hong-ying (Yankuang ceshi, 2020)
BACKGROUND Uranium mineral dating has been difficult to ascertain in mineralization chronology. With the development of in situ U-Pb isotope dating technology, it is possible to directly date ore minerals (uranium minerals). However, due to complex occurrences of sandstone-type U deposits, high requirements for laser ablation during in situ dating, and the lack of suitable external calibration standards, the dating accuracy needs to be improved. OBJECTIVES To solve the problem of shortage of reference materials for in situ U-Pb dating of sandstone-type uranium deposit. METHODS Two micro in situ U-Pb isotope dating methods are used for sandstone-type uranium deposits, attempting to solve the problem of no matrix-matched standards and improve the dating technology of sandstone-type uranium deposits. A laser ablation multi-collector inductively coupled plasma-mass spectrometer combined with an electron probe for micro-area in situ U-Pb isotope dating technology was established (LA-MC-ICP-MS & EMPA). RESULTS By optimizing the analytical technique, the Chenjiazhuang granite-type uranium deposit in Qinling was tested, and the ages were consistent with those determined by the isotope dilution-thermoionization mass spectrometry (ID-TIMS), which demonstrated the feasibility of non-matrix matched reference materials for isotope dating. This method was used to data Hongqinghe and Tarangalle sandstone-type uranium deposits in the Ordos Basin. At the same time, in situ U-Pb isotope dating of Hongqinghe and Ningdong sandstone-type uranium samples was carried out by fs-laser ablation multiple-collector inductively coupled plasma-mass spectrometry (fsLA-MC-ICP-MS). In situ U-Pb isotope ages were obtained for these two deposits, indicating that femtosecond laser ablation technology had a good application prospect in the dating of sandstone-type uranium deposits. CONCLUSIONS Combined LA-MC-ICP-MS and EMPA method can be selected for analysis of simple-texture and relatively old minerals, whereas fsLA-MC-ICP-MS method is recommended for samples requiring high spatial resolution.